2012
DOI: 10.1148/radiol.11111157
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Calcific Tendinitis: Does Warm Saline Solution Improve the Short-term Outcome of Double-Needle US-guided Treatment?

Abstract: Purpose:To determine whether saline temperature infl uences procedure performance and outcome in patients undergoing ultrasonography (US)-guided lavage for the treatment of rotator cuff calcifi c tendinitis (RCCT). Materials and Methods:This study was approved by the institutional review board, and informed consent was obtained from all patients. , and analysis of variance tests. Results:Procedure duration was signifi cantly shorter ( P , .001) in patients treated with warm saline (mean, 576 seconds 6 121) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 18 publications
2
77
1
1
Order By: Relevance
“…They found shorter procedure time and easier dissolution of calcium deposits. 42 VAS was not different between saline temperature groups, but bursitis incidence was less in warm saline treated patients.…”
Section: Injectionsmentioning
confidence: 69%
See 2 more Smart Citations
“…They found shorter procedure time and easier dissolution of calcium deposits. 42 VAS was not different between saline temperature groups, but bursitis incidence was less in warm saline treated patients.…”
Section: Injectionsmentioning
confidence: 69%
“…These techniques may utilize two needles 24,41,42 or one. [43][44][45][46][47][48] The technique is often performed as follows ( Fig.…”
Section: Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 According to the ultrasound appearance, calcific deposits can be classified as hard (hyper-reflexive nodule with a well-circumscribed dorsal acoustic shadow), soft (wellcircumscribed, homogeneous hyperechoic foci without posterior shadow) and fluid (hyperechoic peripheral rim with hypoechoic/anechoic centre). [15][16][17] Being a self-healing process, asymptomatic cases of calcific tendinopathy do not usually require treatment. In patients with mild symptoms, the disease can be managed conservatively with physical therapy and a short course of oral NSAIDs.…”
Section: Treatment Of Calcific Tendinopathy Of the Rotator Cuffmentioning
confidence: 99%
“…10,12 Percutaneous treatment is not indicated if the calcification is asymptomatic, is very small (,5 mm), has migrated into the bursal space or is eroding the humeral cortical bone. 26 Since the first study performed by Farin et al, different techniques and approaches have been reported in the literature 12,15,17,23,27,28 using one or two needles of different sizes to remove calcium. To date, no evidence exists in favour of using a specific size or number of needles.…”
Section: Treatment Of Calcific Tendinopathy Of the Rotator Cuffmentioning
confidence: 99%